Инфекционные и инвазионные болезни лошадей - Лекарев Василий Михайлович (Сельхозгиз, 1954)
Экземпляры: КХ (20180315) / Инвентарный номер: 174419 / Сис.шифр: 636.1.09 / Авт.знак: И 74 / ГРНТИ: 68.41 / ББК: 46